Food hygiene knowledge, and practices and their associated factors of street food vendors in Gondar city, Northwest Ethiopia, 2021: A cross-sectional study. Issue 11 (November 2022) - Azanaw, Jember; Engdaw, Garedew Tadege; Dejene, Hanna; Bogale, Samual; Degu, Siraye
Abstract: Background: Death and illness because of food-borne diseases have greater than previously. According to WHO 2015 report, food-borne diseases affect more than 1/3 of the total population in developing countries each year. Risky food preparation and handling by Street food vendors have made food safety concern for public health. Most individuals nowadays have their meals outside their homes, which are vulnerable to disease caused by contaminated food. This study aimed at assessing the food safety knowledge, and self-reported practices and their associated factors among street food vendors in Gondar city, Northwest Ethiopia. Methods: A cross-sectional study was conducted to assess food safety knowledge, practices, and their associated factors among 395 street food vendors, which were selected randomly from 700 street food vendors. The data was collected from September 10–28, 2021. Data collection was through face-to-face interview. Then, only fully completed questionnaire were considered for analysis. The data analysis was done using Stata Version 14. Descriptive statistics, binary logistic regression and Spearman's correlation analysis were done. Probability less than to 0.05 was considered statistically significant. Results: More than half of vendors are licensed (56.5%). Over three-fourths (79.7%) of the food vendors have information about food safety and hygienic practice. Nearly half (50.6%) and 50.9% of study subjects were poor in food hygiene knowledge and practice respectively. Significant relationships were found between knowledge and practice (β1 = 0.46, p < 0.001), and also knowledge and attitude ((β1 = −0.38, p < 0.001). Male food vendors (AOR: 2.05, 95% CI (1.25, 3.10)), food vendors with poor food hygiene attitude (AOR: 2.54, 95% CI (1.65, 3.90)), and those not receive feedback from the customers on food hygiene (AOR: 2.14, 95% CI (1.40, 3.27)) were poor in food hygiene knowledge. Street food vendors who were non-licensed (AOR: 2.06, 95% CI (1.33, 3.17)), no food hygiene information (AOR: 3.03, 95% CI (1.73, 5.31)), and had no training (AOR: 1.26, 95% CI (1.78, 2.04)) were poor in food hygiene practice. Conclusion: The overall findings of this study indicated that around half of street food vendors' food hygiene knowledge and practices were poor. Sex, food hygiene attitude, and feedback from customers were significantly associated factors with food hygiene knowledge. In addition, licensing status, food hygiene information, and training related to food hygiene were statistically associated factors with the food hygiene practice. Significant relationships were found between food safety knowledge and food safety practice and also knowledge and attitude. Abstract : Food safety; Food vendors; Knowledge; Attitudes-practice; Ethiopia.